Inhibitory Selection Mechanisms in Clinically Healthy Older and Younger Adults. (14th March 2016) - Eich, Teal S; Gonçalves, Beatriz M M; Nee, Derek E; Razlighi, Qolamreza; Jonides, John; Stern, Yaakov
Abstract: Objective: Declines in working memory are a ubiquitous finding within the cognitive-aging literature. A unitary inhibitory selection mechanism that serves to guide attention toward task-relevant information and resolve interference from task-irrelevant information has been proposed to underlie such deficits. However, inhibition can occur at multiple time points in the memory-processing stream. Here, we tested whether the time point at which inhibition occurs in the memory-processing stream affects age-related memory decline. Method: Clinically healthy younger ( n = 23) and older ( n = 22) adults performed two similar item-recognition working memory tasks. In one task, participants received an instruction cue telling them which words to attend to followed by a memory set, promoting perceptual inhibition at the time of encoding. In the other task, participants received the instruction cue after they received the memory set, fostering inhibition of items already in memory. Results: We found that older and younger adults differed in their ability to inhibit items both during encoding and when items had to be inhibited in memory but that these age differences were exaggerated when irrelevant information had to be inhibited from memory. These results provide insights into the mechanisms that support cognitive changes to memory processes in healthy aging.